Effect of Numbers of Fringing Electric Field (FEF) Fingers on the Performance of Sensor for Water Content in Soil - Azman, Mohd Farizul; Yahya, Azmi; Purwanto, Hadi (International Association of Computer Science and Information Technology Press (IACSIT Press), 2013)
The Fringing Electric Field (FEF) element design consideration has been discussed in this paper. This type of sensor is planned to be used for the Non-Destructive Test (NDT)measurement of a moisture level in soil for irrigation system in the field and green house. The effect of soil type and its moisture level has been taken into account by preparing several types of soil moisture level in the lab by performing measurement and calculation as proposed by several papers. It has been shown that the FEF parameters such as the dielectric constant, numbers of finger for FEF design and the working frequency played an important role for FEF design considerations. The performance of the FEF element sensor had been compared with the commercial sensor for benchmarking.